Donorship as a component of humanistic education of medical students - L. I. Ilyenko; T. G. Muradyan; N. V. Orlova; M. A. Nechmir; A. M. Nekrasova (Кардиоваскулярная терапия и профилактика)
Aim. Humanistic education of students through involvement in blood donation.Material and methods. A survey of 4020 participants of the Donor Day was conducted at the Pirogov Russian National Research Medical University with subsequent analysis and statistical processing of the data obtained.Results. The development of donation within the educational extracurricular activities has made it possible to increase the number of donors in the Pirogov Russian National Research Medical University to 2000 people. According to the survey, 88,6% of respondents put forward the motivation to help those in need in the first place, while 44,2% consider donation to be beneficial for health, and 24,4% consider donation to be their civic duty. In addition, 9,2% donate blood due to the fact that friends or relatives benefited from blood transfusions. Departure of a team of specialists from blood service institutions to the university was recognized as the best format. There were following reasons for refusing to participate in the donorship: 17,5% do not know where and how to become a donor, 16,0% are sure that health will worsen during donation, 14,4% do not find free time, 11,4% are not satisfied the location of blood service institutions, and 13,7% avoid problems with the employer or the university. Since 2020, our own register of bone marrow donors has been created, which is part of the Federal Register of Bone Marrow Donors. More than 1000 students entered the Register, while 9 donated bone marrow for patients.Conclusion. Educational work with medical students should include the popularization of donation, as the formation of a moral and ethical standard and civic duty. It is necessary to inform students about donation, create comfortable conditions and route donors.